Impact of generic antiretroviral drugs introduction on pharmaceutical expenditure patterns in the Netherlands: a six-year retrospective database analysis from 2016 to 2022 - P. Oosterhof; M. Van Luin; J. W. Vanhommerig; K. Brinkman; D. M. Burger (BMC Health Services Research)
Abstract Background In the Netherlands, the annual expenditure on HIV care was reported as €202 million in 2019, with about 70% allocated to antiretroviral therapy (ART). The introduction of generic antiretroviral medications (ARVs) in 2017 has offered potential cost-saving opportunities in healthcare. Understanding the financial implications of incorporating generic ART into the Dutch healthcare system is crucial to determine its impact. Methods We used data from the Foundation for Pharmaceutical Statistics (SFK), covering 98% of all community and outpatient clinic pharmacies across the Netherlands. This dataset contained medication information from 2016 to 2022. Medication data were classified using the Anatomical Therapeutic Chemical Classification with Defined Daily Dose (ATC/DDD) system. Cost analysis was based on Dutch drug prices ( www.medicijnkosten.nl ) for a specified period, and the data were processed using IBM SPSS. Results In the Netherlands, people with HIV receiving ART increased from 20,072 to 24,573 between 2016 and 2022. HIV medication expenditure was €190 million euros in 2016, with generic medication at 6% DDDs. After an increase in 2017, a subsequent decrease in total HIV medication expenditure led to an overall cost of €181 million in 2022 (-5.1% compared to 2016). Simultaneously, the proportion of DDDs dispensed as a generic increased to 16–32% over the years. This could be linked to 97% compliance with generic substitutions for ARVs where a generic equivalent was available. Notably, the cost per patient per year has declined from €9,488 in 2016 to €7,352 in 2022 (-22.5% compared to 2016). Some of the potential cost-savings through generic substitution were not utilized because of the 20% point increase in the use of novel branded single-tablet regimens (STRs). Conclusions Our analysis showed high compliance with generic substitution of ARVs in the Netherlands. The increased use of generic ARVs was accompanied by an almost 10% reduction in overall expenditure on ART despite a significant increase in the number of patients in care in the Netherlands during this period. A significant contributing factor to ART costs appears to be the high percentage of prescribed patented Single-Tablet Regimens (STRs). These findings underscore the complex dynamics of pharmaceutical expenditures in the Dutch healthcare system.